Examining Customer Loyalty in AYCE Dining: A Qualitative Investigation of Experience-Driven Factors - Utomo, Sherly; Prawira, Mega Fitriani Adiwarna (Journal of Tourism Sustainability, 2024)
The all-you-can-eat (AYCE) restaurant model has gained popularity by offering unlimited food at a fixed price, attracting customers seeking variety, value, and social engagement. However, customer loyalty in AYCE settings remains underexplored, as existing models focus on service quality and customer satisfaction, overlooking experiential factors that drive retention. This study addresses this gap by identifying key psychological, social, and hedonic dimensions shaping AYCE customer loyalty and proposing a new conceptual model. Using a qualitative exploratory approach with grounded theory methodology, this study conducted semi-structured interviews and participant observations in AYCE restaurants across West Java, Indonesia. A total of 25 participants—20 customers and five industry practitioners—provided insights into dining behaviors and operational strategies. Findings reveal three core determinants of AYCE customer loyalty: psychological comfort, social bonding, and perceived food abundance. Customers valued dining autonomy, fostering a relaxed experience, while social bonding reinforced emotional connections through shared meals. Perceived food abundance enhanced hedonic satisfaction, strengthening value-for-money perceptions. However, when variety exceeded quality expectations, dissatisfaction emerged, highlighting the need to balance quantity and quality. This study introduces a conceptual model positioning customer satisfaction as a mediating factor between experience-driven motivators and loyalty outcomes. The findings expand experience-based loyalty research and offer practical insights for AYCE operators.